Molecular characterization of rotavirus diarrhea among children aged under five years in the Philippines, 2013–2015. Issue 51 (14th December 2018) - Bonifacio, Joseph; Lupisan, Socorro; Roque, Vito; Ducusin, Maria Joyce; Grabovac, Varja; Batmunkh, Nyambat; Heffelfinger, James D.; Fox, Kimberley; Toda, Kohei; de Quiroz Castro, Maricel; Kirkwood, Carl; Tandoc, Amado
Abstract: With the availability of new and existing rotavirus vaccines, credible and reliable data on burden of rotavirus-associated disease are needed to enable evidence-based decision making regarding the introduction of rotavirus vaccines. The national rotavirus surveillance program in the Philippines, a sentinel-based surveillance, was established in 2012 to determine the proportion of laboratory-confirmed rotavirus cases among children under five years with acute gastroenteritis and to describe the geographic distribution and molecular epidemiology of rotavirus in the country. During 2013 to 2015, rotavirus infection was the cause of acute gastroenteritis among children under five years admitted to hospitals or evaluated in emergency rooms, constituting more than one-third of gastroenteritis hospitalizations at the sentinel site hospitals. The predominant genotype observed was G1P[8]. Although a rotavirus surveillance network has been established, findings suggest the need to strengthen the network in the country and to continue monitoring prevalent rotavirus strains to help identify the possible emergence of new strains.